Perception of episiotomy among pregnant women in Kano, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Episiotomy can be defined as a surgical incision made at the perineum to widen the introitus and facilitate delivery.Objective:To assess the perception of women on episiotomy.Design:A prospective cross sectional study.Settings:This was the antenatal clinic of Aminu Kano Teaching Hospital, Kano.Methods:All consented pregnant women at booking were recruited and interviewed.Results:Over the six weeks period of the study, 109 women were interviewed. Majority of the women (94.5%) have heard of episiotomy and 81.7% were able to describe it as a surgical incision to facilitate delivery. Most of their sources of information were from friends/relatives (52.3%). Fifty seven (52.3%) out of the 109 women have had episiotomy and ‘Big baby’ as described was the commonest indication for the episiotomy (62.5%). Majority of the women (66.1%) Did not have prior counselling before episiotomy and 76.8% Did not have any complication following the repair. Most of the women (69.6%) had their episiotomies repaired within an hour of delivery. Twenty eight (49.1%) out of the 56 women who had episiotomy do not believe women should be routinely given episiotomy at delivery while 40.4% of the women were of the opinion that it should be routine to avoid injury to the baby. Majority of the women (82.1%) advocated for anaesthesia prior to episiotomy.Conclusion:There is a good knowledge of this procedure among pregnant women in AKTH Kano.